Biomimétisme : outils pour une démarche écoinnovante en ingénierie - Philippe Terrier; Mathias Glaus; Emmanuel Raufflet (VertigO, 2017)
Ensure that innovation contributes to the development of engineering solutions in harmony with the limits of the environment ! This is what is offered by the biomimicry design approach. After the general presentation of the concept of biomimicry, the emphasis will be placed on methods and practical biomimetic tools to facilitate ideas generation and innovation in engineering. The proposed methods are like a toolbox to serve ecoinnovation. We find in this group of solutions, approaches based on the consultation of the Ask Nature database, the use of design card, and the BioTRIZ method which will all be presented in this article. The warnings that must be known and the methodology for the implementation of the biomimetic approach in engineering will be presented.